Penerapan Pendekatan Keadilan Pestoratif oleh Kepolisian Negara Republik Indonesia dalam Penyelesaian Tindak Pidana di Wilayah Hukum Polres Payakumbuah - Kurniawan, Iwan; Nelwitis, Nelwitis; Afrizal, Riki (Faculty of Law, Andalas University, 2023)
In Indonesia's criminal justice system, imprisonment is a sanction commonly imposed on perpetrators of criminal acts. This condition is not in line with Indonesian society, which is a communal society that prioritizes solving problems through deliberation and consensus. Therefore, there is a tendency in Indonesian society to use a restorative justice approach in resolving criminal law problems. This approach has been recognized and adopted by law enforcement agencies such as the Police. This approach has been adopted in the Republic of Indonesia State Police Regulation (Perkap) Number 8 of 2021 concerning the Guideline for Handling Criminal Acts Based on Restorative Justice. This approach is a new paradigm in the strategy for handling criminal cases by the Police. Resolving criminal acts through this approach also involves the perpetrator, victim, victim's family, community leaders, religious leaders, and traditional leaders in seeking a peaceful resolution by restoring the original situation. This research aims to study how the restorative justice approach is run by the Police in solving a criminal case at Payakumbuh Police Region and the obstacles faced by the Police. The research is carried out through sociological–juridical legal research emphasizing field research. In addition, this research also applies a study of existing legal materials. This descriptive research intends to describe the reality studied clearly and systematically. This research finds that the Payakumbuh Police officers have implemented this restorative justice approach to most criminal cases. In implementing this approach, the police officers encountered several juridical and non-juridical obstacles. Legal obstacles relate to the multi-interpretation of a legal norm, while practical obstacles are complicated procedures, difficulties finding an agreement, and compensation issues.